Biomedical engineering systems and technologies : 11th International Joint Conference, BIOSTEC 2018, Funchal, Madeira, Portugal, January 19-21, 2018, Revised selected papers /: 11th International Joint Conference, BIOSTEC 2018, Funchal, Madeira, Portugal, January 19-21, 2018, Revised selected papers. (2019) - Unknown
No abstract available